2018
DOI: 10.1002/jcph.1360
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Tofacitinib Concentrations in Adult Patients With Atopic Dermatitis Treated With 2% Tofacitinib Ointment and Application to Pediatric Study Planning

Abstract: Atopic dermatitis is a chronic eczematous, pruritic, inflammatory skin condition affecting children and adults. Tofacitinib is a Janus kinase inhibitor. The efficacy, safety, and pharmacokinetics of 2% tofacitinib ointment twice daily have been evaluated in a 4‐week phase 2a multisite randomized, double‐blind, vehicle‐controlled, parallel‐group study (NCT02001181) in adult patients with mild to moderate atopic dermatitis and 2% to 20% body surface area (BSA) involvement. Tofacitinib ointment demonstrated signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 26 publications
0
26
1
1
Order By: Relevance
“…Among patients with atopic dermatitis who were applying tofacitinib 2% ointment over limited areas, 24% had plasma concentrations of the drug greater than 1 ng/mL a mean of 0.6 hours later. 8 For comparison, the mean concentration after a 5-mg oral dose, as used in rheumatoid arthritis, is approximately 17.0 ng/mL. 8 The plasma concentration with topical treatment in some patients may be sufficient to produce a therapeutic response at distal lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among patients with atopic dermatitis who were applying tofacitinib 2% ointment over limited areas, 24% had plasma concentrations of the drug greater than 1 ng/mL a mean of 0.6 hours later. 8 For comparison, the mean concentration after a 5-mg oral dose, as used in rheumatoid arthritis, is approximately 17.0 ng/mL. 8 The plasma concentration with topical treatment in some patients may be sufficient to produce a therapeutic response at distal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…8 For comparison, the mean concentration after a 5-mg oral dose, as used in rheumatoid arthritis, is approximately 17.0 ng/mL. 8 The plasma concentration with topical treatment in some patients may be sufficient to produce a therapeutic response at distal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The Janus kinase (JAK) inhibitor, tofacitinib (28), was developed originally for management of rheumatoid arthritis, ulcerative colitis and other autoimmune diseases, but it was repurposed for psoriasis and atopic dermatitis since JAK was found to be contributing in the pathogenesis of these diseases, and currently, several clinical trials were performed to assess its clinical significance and concluded that response rates in tofacitinib-treated group were significantly higher compared to that in placebo [39][40][41].…”
Section: Clinical Observation-based Drug Repurposingmentioning
confidence: 99%
“…By avoiding treatment of pregnant mothers, the primary side effect (birth defects) is avoided. A recent study of the topical pharmacokinetics of tofacitinib (Purohit et al, 2019) illustrates a general observation that topical application of a drug to a body surface area of <30% rarely leads to a systemic drug concentration sufficient to lead to side effects. Repositioning can therefore be a particularly effective strategy in dermatology.…”
Section: Repositioningmentioning
confidence: 99%